Monocentric or Polycentric? Defining Morphological Structure of NUTS-2 regions of Turkey from 2000 to 2016 - Sat, N. Aydan (Geographica Pannonica, 2017)
The popularity of polycentricity has been increasing in recent years. European spatial planning literature and policy documents that emphasize the positive effects of polycentricity can be one of the reason increase in the popularity of the concept. Although not as clear and planned as in European countries, it is argued that, Turkey's metropolitan cities are also evolving from monocentric spatial structure to polycentric ones. However, there is no empirical study on the measurement of this spatial evolution at national and micro-regional scale in Turkey. From this point of view, this study aims to clarify changes in the morphological structure of Turkey from 2000 to 2016 at national and micro-regional scales and to examine the proposition of ‘the spatial configurations of the settlements, especially metropolitans, have  been evolving from monocentric to polycentric as results of the dynamics of the 21st century’ in Turkey case. The results of empirical analyses show that there is a possibility for Turkey to be a more monocentric in following years if the historical trends continuous.